The effect of maternal high-risk fertility behavior on child nutritional status in Sub-Saharan Africa: a propensity score-matched analysis - Seifu, Beminate Lemma; Asebe, Hiwot Atlaye; Fente, Bezawit Melak; Melkam, Mamaru; Asmare, Zufan Alamrie; Asnake, Angwach Abrham; Bezie, Meklit Melaku; Negussie, Yohannes Mekuria (Frontiers in Public Health, 2025)
IntroductionMaternal high-risk fertility behaviors (HRFBs) represent a multifaceted bio-demographic factor with profound implications for child health. Maternal HRFBs raise the risk of undernutrition in children under the age of five, rendering them more susceptible to stunting and wasting. When estimating the impact of HRFBs on child malnutrition using an observational study such as the Demographic and Health Survey (DHS), it’s important to consider the potential for selection bias and the effect of confounding variables. To address this, we employed propensity score-matched (PSM) analysis to more accurately estimate the true impact of maternal HRFBs on children’s nutritional status.MethodsSecondary data analysis of 161,179 children under the age of five was conducted based on the 26 Sub-Saharan Africa DHS data (2015–2023). To estimate the maternal HRFBs on children’s nutritional status, We employed propensity score matching (PSM) with a logistic model using the ‘psmatch2 ate’ STATA command to estimate the Average Treatment Effect (ATE) for the population, the treated group (ATT), and the untreated group (ATU). We assessed the quality of matching both statistically and graphically. Additionally, we conducted a sensitivity analysis to test the robustness of the PSM estimates, using the Mantel–Haenszel (MH) test statistic.ResultsMore than two-thirds of (57.14, 95%CI: 56.90, 57.39) mothers had a high-risk fertility behavior. In SSA the prevalence of stunting, wasting, and being underweight among under-five children was 30.58% (95%CI: 76.30, 76.72), 6.74% (95%CI: 6.62, 6.86) and 16.70% (95%CI: 16.52, 16.88), respectively. The difference in the Average Treatment Effect (ATE) of maternal HRFBs on stunting, wasting, and underweight was 2.00, 0.30, and 2.19%, respectively. The Average Treatment Effect on the Treated group (ATT) showed a 2.12% increased risk of stunting, a 0.24% decreased risk of wasting, and a 2.68% increased risk of underweight. These estimates remained robust to hidden bias and demonstrated good matching quality.ConclusionThese results indicate the necessity of public health interventions aimed at enhancing maternal and child health by promoting family planning services, educating young mothers, and providing support to women with high parity.